PENINGKATAN HOPE PADA MAHASISWA PATTANI THAILAND DI PEKANBARU MELALUI PSIKOEDUKASI - Ulfa, Intan Jamilah; Siregar, Juliarni (EJOIN : Jurnal Pengabdian Masyarakat, 2024)
This study aims to increase the level of academic hope among Patani, Thailand students studying in Pekanbaru, Indonesia. According to Snyder, hope is one of the key factors influencing academic success. Recent data shows that the dropout rate in Pekanbaru is 10%, caused by various factors such as difficulties in cultural adaptation, language barriers, financial problems, and academic pressure. This research uses a quantitative approach involving 52 Patani students at the Islamic University of Riau. The interventions implemented include psychoeducation training, mentoring programs, and psychosocial support. Academic hope was measured using Snyder's Adult State Hope through pretest and posttest. The pretest results showed that 11% of students had low hope, 78% had moderate hope, and 11% had high hope. After the intervention, posttest results showed a decrease to 6% in low hope, 33% in moderate hope, and an increase to 61% in high hope. The increase in academic hope is expected to significantly reduce the dropout rate.